Question and Answers Forum

All Questions      Topic List

Differentiation Questions

Previous in All Question      Next in All Question      

Previous in Differentiation      Next in Differentiation      

Question Number 131887 by Algoritm last updated on 09/Feb/21

Answered by SEKRET last updated on 09/Feb/21

 Leybnist   formula    u= e^(−2x)          u^n =(−2)^n ∙e^(−2x)    v= (1/( (√(1−x))))      v^n =(((2n−1)!!)/(2^n (1−x)^((2n+1)/2) ))  y=uv  y^n =C_n ^0  u^n ∙v+C_n ^1 u^(n−1) ∙v^1 +C_n ^2 u^(n−2) ∙v^2 +....+C_n ^n  u^1 ∙v^n

Leybnistformulau=e2xun=(2)ne2xv=11xvn=(2n1)!!2n(1x)2n+12y=uvyn=Cn0unv+Cn1un1v1+Cn2un2v2+....+Cnnu1vn

Answered by mathmax by abdo last updated on 10/Feb/21

y(x)=e^(−2x) (1−x)^(−(1/2))  ⇒y^((n)) (x)=Σ_(k=0) ^n  C_n ^k {(1−x)^(−(1/2)) }^((k)) (e^(−2x) )^((n−k))   we have (e^(−2x) )^()n−k)) =(−2)^(n−k)  e^(−2x)   let find (1−x)^p }^((k))   {(1−x)^p }^((1))  =p(−1)(1−x)^(p−1)   {(1−x)^p }^((2))  =p(p−1)(−1)^2 (1−x)^(p−2)  ⇒  {(1−x)^p }^((k))  =p(p−1)....(p−k+1)(−1)^k (1−x)^(p−k)  ⇒  {(1−x)^(−(1/2)) }^((k) ) =(−1)^k (−(1/2))(−(3/2))....(−(1/2)−k+1)(1−x)^(−(1/2)−k)  ⇒  y^((n)) (x)=Σ_(k=0) ^n  C_n ^k   (−1)^k (−(1/2))(−(3/2))....(−(1/2)−k+1)(1−x)^(−(1/2)−k) (−2)^(n−k)  e^(−2x)

y(x)=e2x(1x)12y(n)(x)=k=0nCnk{(1x)12}(k)(e2x)(nk)wehave(e2x))nk)=(2)nke2xletfind(1x)p}(k){(1x)p}(1)=p(1)(1x)p1{(1x)p}(2)=p(p1)(1)2(1x)p2{(1x)p}(k)=p(p1)....(pk+1)(1)k(1x)pk{(1x)12}(k)=(1)k(12)(32)....(12k+1)(1x)12ky(n)(x)=k=0nCnk(1)k(12)(32)....(12k+1)(1x)12k(2)nke2x

Terms of Service

Privacy Policy

Contact: info@tinkutara.com